Veterinary nanomedicine: Pros and cons. Issue 1 (29th December 2022) - Jafary, Fariba; Motamedi, Shima; Karimi, Isaac
Abstract: In recent years, nanotechnology has improved life with continuous growth in different fields. Nanoparticles can be employed in industry, imaging, engineering, and various biomedical filed because of their special physicochemical properties like rapid, effective, highly specific solutions, higher stability, biodegradability, biocompatibility, and cost. In this line, veterinary medicine has been influenced by nanotechnology in prevention, diagnosis, and treatment of diseases, cancer therapy, immunization, vaccine production, drug delivery, and health besides to related issues of animal production, maintenance, and welfare. The other important point is the interwoven linkage between animals and humans whether as a food source or as a companionship. Inorganic nanoparticles, polymeric, solid lipid, liposomal, nanocrystal, nanotubes, nanoemulsions, micelles, mesoporous silica nanoparticles, and dendrimers are kinds of nanoparticles that can be used widely. In this review, the impacts of nanotechnology on veterinary medicine have been summarized, criticized, and acknowledged as "veterinary nanomedicine" discipline. Abstract :